#UsToo How Jewish, Muslim, and Christian Women Changed Our Communities - McGinity, Keren R. (Global Gender, 2024)
#UsToo: How Jewish, Muslim, and Christian Women Changed Our Communities examines the relationship between sexual harassment, gender, and multiple religions, highlighting the voices of women of different faiths who found their voices and used them for the betterment of their communities. Through personal interviews and other research, this book explores the actions of American Jewish, Muslim, and Christian women who broke the silence about sexual misconduct and abuse of power by male co-religionists. Using a three-dimensional, ethnoreligious approach that examines gender, ethnicity, and religion, it addresses the relationship between religion and women's experiences and examines both historical contexts and present-day experiences of sexual misconduct within faith communities. This book will be of key interest to students within Gender Studies, History, Religion, and Sociology, clergy and lay religious leaders, and human rights advocates.